Programme de formation clinique dans les communautés francophones en situation minoritaire du Consortium national de formation en santé - Volet La Cité - Boulet, Mélanie (Reflets, 2018)

Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

Exploration of English language program undergraduate nursing students’ attitudes toward the risks of English-French language discordance and their implementation of the active offer of French language health services in Ontario [master's thesis, University of Ottawa] - Ford, Amy (University of Ottawa, 2018)
As has been reported in Canadian research on the experiences of Francophone patients and Francophone health professionals, active offer is not common or well performed in the Ontario healthcare system (Bernier, 2009; Boileau, 2016; Bouchard & Desmeules, 2013; Drolet et al., 2014; Hien & Lafontant, 2013). This descriptive quantitative research explored the self-reported awareness and implementation of the active offer concept during clinical placements by English language program 4th year undergraduate nursing students. A total of 69 participants were recruited in April 2017 to complete a paper or online-based survey. The survey consisted of questions on French language abilities, awareness of the patient safety risk of language discordance, communication experiences with Francophone patients and opinions of the role of the nurse, healthcare organizations and universities in the implementation of active offer. The participating nursing students reported little knowledge and training for implementing active offer during clinical settings. Despite the lack of preparation, the majority of them (92%) reported caring for a Francophone patient at least once with 25% doing that eight times or more during their clinical placements. More than 84% reported finding a way to communicate with Francophone patients in French, by speaking to them in French themselves or by asking Francophone colleagues, a professional interpreter or the patients’ family to interpret for them. Study recommendations include training nursing students during their undergraduate studies about the patient safety risks of language discordance, active offer and how to implement it. All English program nursing students should also be taught how to access and work with a professional interpreter. Those with French language skills should be encouraged to take healthcare specific language training. New research should be done to explore communication between English language program nursing students and Francophone patients to identify if it is safe and adequate from both the student and the patient’s point of view.

Stages et réalité des professionnelles et professionnels en santé et services sociaux dans un contexte francophone minoritaire à Iqaluit, au Nunavut - Mercure, Dominique; Rivard, Sylvie; Bélanger, Roxanne; Charrier, Marie-Josée (Reflets, 2018)
Cet article présente la démarche d’analyse et les résultats d’une recherche sur les stages et la réalité des professionnelles et professionnels en santé et services sociaux dans un contexte francophone minoritaire en région arctique. Une démarche méthodologique d’étude de cas à multiples niveaux a été choisie pour permettre de comprendre le vécu des différents acteurs et actrices de la communauté francophone vivant à Iqaluit, au Nunavut. Douze entretiens ont été effectués auprès de stagiaires et de professionnelles et professionnels oeuvrant dans les services de santé et les services sociaux pour mieux saisir leur contexte de pratique, les défis rencontrés, les compétences développées dans ce milieu et les obstacles quant à l’organisation des stages. Les résultats illustrent les perceptions de participantes et participants non autochtones sur une réalité complexe composée de nombreux défis. Mots-clés : stages en région éloignée, Iqaluit (Nunavut, Canada), communauté francophone en situation minoritaire (CFSM), défis professionnels et personnels en milieu de stage, pratique professionnelle en contexte interculturel

Enjeux relatifs à la formation en français dans le domaine des sciences infirmières. Rapport du Comité permanent des langues officielles - Paradis, Denis (Gouvernement du Canada, Chambre des communes 42e Législature, 1re session, 2018)

Des stages en français pour se préparer à travailler auprès communautés francophones en situation minoritaire - Savard, Jacinthe; Benoît, Josée; Dubouloz, Claire-Jehanne; Breau-Godwin, Stéphanie (Reflets, 2018)
Dans l’objectif d’augmenter le nombre de professionnelles et professionnels pouvant offrir des services sociaux et de santé en français dans les communautés francophones en situation minoritaire (CFSM), des stages en français ont été offerts à des étudiantes et étudiants bilingues de programmes de formation professionnelle offerts en anglais au sein d’universités canadiennes. L’expérience a été positive pour l’ensemble des parties prenantes : stagiaires, éducatrices-cliniciennes et responsables de la formation clinique. Après cette expérience, les stagiaires ont mentionné avoir une meilleure connaissance des défis d’accès aux services rencontrés par les CFSM et se sentir plus en mesure d’offrir des services en français à ces communautés. Mots-clés : stage en français, formation clinique, communautés francophones en situation minoritaire, offre active, réadaptation

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

L’infirmière psychiatrique, leader de l’équipe multidisciplinaire : étude de cas, Hôpital Montfort, 1976-2002 - Valentina Moya, Silvia. Maria (L’infirmière psychiatrique, leader de l’équipe multidisciplinaire : étude de cas, Hôpital Montfort, 2018)
Cet article a pour but de présenter l’espace relationnel de l’infirmière psychiatrique, dans un contexte de prestation de soins en français à Ottawa, pendant la période de désinstitutionnalisation psychiatrique. L’étude de cas d’une patiente francophone suivie pendant 26 ans à la clinique externe de l’Hôpital Montfort a été choisie comme échantillon. Durant son parcours de vie psychiatrique, 63 % des contacts de cette patiente ont été avec l’infirmière, 27 % avec les psychiatres, 5 % avec les ergothérapeutes, 4 % avec les travailleurs sociaux et 1 % avec les psychologues. Parmi les différentes tâches documentées par les infirmières, on retrouve six différents types d’intervention. Le dossier étudié révèle donc que l’infirmière occupe un espace relationnel plus important que les autres professionnels de l’équipe multidisciplinaire. Mots-clés : infirmière, santé mentale, désinstitutionnalisation psychiatrique, équipe multidisciplinaire, parcours de vie